Electrochemical Fabrication of Hybrid Plasmonic-dielectric Nanomaterial Based on Gold-diamond Clusters - Tung, Do Hoang; Thuong, Tran Thi; Liem, Nguyen Thanh; Duong, Pham Van; Lien, Nghiem Thi Ha; Minh, Pham Hong; Ionin, Andrey Alekseevich; Levchenko, Alexey Olegovich; Rudenko, Andrey Andreevich; Saraeva, Irina Nikolaevna; Ivanova, Anastasiya Konstantinovna; Kudryashov, Sergey Ivanovich; et al. (Communications in Physics, 2017)
Hybrid plasmonic-dielectric material were fabricated by micro-discharge through water sols of sub-micrometer-sized diamonds mixed with HAuCl4 acid. Primary characterization of their deposits on a silicon wafer surface by means of electron microscopy and energy-dispersive x-ray spectroscopy indicate close proximity of gold nanoparticles and diamond particles, which is supported by photoluminescence studies demonstrating strong – almost two-fold – damping of diamond luminescence owing to the attachment of gold nanoparticles. UV-near IR spectroscopy of their sols consistently exhibits small red spectral shifts for the fabricated nanomaterial, comparing to bare gold nanoparticles. Keywords: micro-diamonds, gold nanoparticles, hybrid plasmonic-dielectric material, electrochemical fabrication, electron microscopy and optical characterization